2019
DOI: 10.1021/acs.jpcc.9b02272
|View full text |Cite
|
Sign up to set email alerts
|

Computational Evaluation of the Oxidative Cleavage of Triazine Derivatives for Electrosynthesis

Abstract: Computational chemistry was used to study the N-C bond dissociation Gibbs free energies (298 K, acetonitrile) for a test set of 54 triazine derivatives, comprising combinations of 6 triazinyl radicals with 9 different alkyl leaving group. Results were obtained for homolytic cleavage of the neutral compound, and two possible mesolytic cleavage pathways for the oxidized form (cleavage to a triazinyl radical and a carbocation, or cleavage to a triazinyl cation and a carbon-centered radical). Oxidation potentials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Triazinyls considered in our previous work (ref ). Substituents “X” and “Y’ are consistent with those in the verdazyl series of Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Triazinyls considered in our previous work (ref ). Substituents “X” and “Y’ are consistent with those in the verdazyl series of Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…We very recently illustrated, in silico, that R-groups attached to electron rich benzo-1,2,4-triazinyl radicals form adducts that are far better candidates for • cleavage, owing to their very low oxidation potentials (-0.7 -0.2 V for radicals, and -0.3 -0.4 V for adducts). [7][8][9] We found that for all derivatives considered, it should be possible to drive the cleavage of more electron rich…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Blatter radicals have also been used in chemical synthesis. For example, they can act as initiators in controlled polymerizations, [35][36][37][38] as organic paramagnetic ligands in metal coordination complexes, [39][40][41] and as building blocks in high-spin diradicals and biradicaloids. 32,42,43 Blatter-type radicals can form stable thin films (without degradation) while retaining their paramagnetic character.…”
mentioning
confidence: 99%